Deer Rescue in Tuscany: Retrospective Analysis and Assessment of Radiography Diagnoses - Irene Nocera (MDPI AG, 2021)
Animal-vehicle collisions are the major cause of rescue and need for hospitalization in wildlife referral centers. Clinicians need easy-to-use tools to make rapid decisions about whether to euthanize or treat injured animals. The aim of the study was to evaluate the data (reasons for rescue, diagnosed lesions, and outcome) from a hospitalized population of wildlife ungulates and investigate the benefits of using radiography as a diagnostic tool. Data were collected from three wildlife referral centers in Tuscany (Italy). The following information was collected for each animal: reason for hospitalization, clinical examination, radiographic examination, definitive diagnosis, and outcome. A chi-squared test was used to assess the benefits of radiography in detecting different traumatic lesions. Prevalence was reported according to the reason for hospitalization, definitive diagnosis, radiographic diagnosis, and outcome. The main reason for hospitalization was traumatic lesions due to vehicle collisions and 71.1% of the animals did not survive. Radiography was more useful in patients with traumatic axial skeletal lesions and/or multiple traumas with respect to traumatic appendicular skeleton lesions. Our results show that radiography is a useful diagnostic technique for assessing wildlife emergencies and it could help the clinician in making medical decisions.